PENGARUH ETOS KERJA DAN KOMPENSASI TERHADAP KINERJA GURU MELALUI MOTIVASI SEBAGAI VARIABEL INTERVENING DI SDK HARAPAN BANGSA BALIKPAPAN - Sitorus, Hana Flowerens; Fathorrahman, Fathorrahman; Handarini, Dany M. (POLITEKNIK LP3I JAKARTA, 2026)
Education is a fundamental pillar in national development, where the quality of its implementation is largely determined by teachers’ performance as the main actors in the learning process. Teachers play a strategic role not only in delivering instructional content but also in shaping students’ competencies and character. Therefore, teachers’ performance is a crucial indicator of educational institution success. In the context of school organizations, teachers’ performance is influenced by various internal and external factors, including work ethic, compensation, and work motivation. Differences in work attitudes, levels of professional commitment, and reward systems received by teachers represent important phenomena that need to be examined to comprehensively understand teacher performance dynamics. This study aims to analyze the effects of work ethic and compensation on teachers’ performance, both directly and through work motivation as an intervening variable, at SDK Harapan Bangsa Balikpapan. This research employed a quantitative approach using a survey method. The research population consisted of all teachers at SDK Harapan Bangsa Balikpapan, totaling 35 respondents, and a saturated sampling technique was applied, in which the entire population was used as the research sample. The results indicate that work ethic and compensation have a positive and significant effect on teachers’ performance. Work ethic also has a positive and significant effect on teachers’ work motivation. However, compensation does not have a significant effect on work motivation, and work motivation does not have a significant effect on teachers’ performance. Furthermore, work motivation does not function as an intervening variable in the relationship between work ethic and compensation and teachers’ performance.